Obtaining information on the Q-structure of the southern Aegean subduction area by spectral slopes from temporary and permanent networks. - Ventouzi, Ch.; Papazachos, C.; Papaioannou, Ch.; Hatzidimitriou, P.; EGELADOS, working group (Bulletin of the Geological Society of Greece, 2013)
Anelastic attenuation studies have been considered one of the main controlling factors affecting seismic wave propagation, providing important information on the earth’s structure. In order to investigate the attenuation structure of the southern Aegean subduction area, we employed ~400 intermediate depth earthquakes recorded by temporary and permanent networks. Using the recorded waveforms we have calculated a frequency-independent path attenuation operator t* for both P and S waves. Initially an automated method was employed, where t* was automatically calculated by the slope of the acceleration spectrum produced above the corner frequency, fc. Computations were performed in the 0.2-25Hz frequency band, using only spectra with a signal to noise ratio greater than 3, and above the noise level for at least the range 1-4Hz (for S and P waves, respectively). In the second approach, the selection of the segment of the spectrum was carried out manually for optimum fitting. No considerable linear trend revealing dependence of t* with distance could be observed on the original data, whereas strong clustering for different focal depth ranges was observed. The spatial variation of the obtained t* values shows that, in general, along arc stations present low values of t*, while bac k-arc stations show much larger values. The observed t* difference becomes more pronounced as the depth of the earthquakes increases, suggesting a significant localized effect of the high -attenuation (low-Q) mantle wedge, in agreement with independent observation.